Why Do We Punish?: The Case for Retributive Justice - Weiler, Joseph (1978)
The never-ending debate about the substantive and procedural rules in our criminal justice system rarely addresses itself to the most fundamental question- why do we punish at all? The answer to this threshold question has traditionally taken one of two lines, retributionist or utilitarian. On the one hand, there is the view that punishment of the morally derelict is its own justification for it is right for the wicked to be punished. This imperative flows from a view of the very nature of man as a responsible moral agent to whom rewards or punishment should be assessed according to the morality of his choice of behavior. On the other hand, there is the teleological, utilitarian view that the only proper justification for punishment is the prevention or reduction of antisocial behavior. The critical questions which the latter theory asks about any social action, law or institution are to be answered in terms of how much good will it produce, at what cost, and is it worth it? The utilitarian justification for punishment and the popularity of the behavioral model reached its zenith in the 196os. This attitude is displayed in the conclusions of the Ouimet Report which stated confidently that the Committee regards the protection of society not merely as the basic purpose but as the only justifiable purpose of the criminal law in contemporary Canada and that the rehabilitation of the individual offender offers the best long-term protection for society.' The widespread support for the rehabilitative ideal crossed political and ideological boundaries. As attractive as these ideas appeared to their proponents, the force of the rehabilitative ideal on the philosophy of punishment diminished as the empirical reality of this brave new world came into focus. This paper examines the reasons for the displacement of the rehabilitative ideal as the dominant theory of correctional philosophy and will assess the revival of the retributive rationale in its new form in the justification of punishment